Quantitative Determination of Fluorinated Alkyl Substances by Large-Volume-Injection LC/MS/MS—Characterization of Municipal Wastewaters - Schultz, Melissa M. (2006)
A quantitative method was developed for the determination of fluorinated alkyl substances in municipal wastewater influents and effluents. The method consisted of centrifugation followed by large-volume injection (500 μL) of the supernatant onto a liquid chromatograph with a reverse-phase column and detection by electrospray ionization, and tandem mass spectrometry (LC/MS/MS). The fluorinated analytes studied include perfluoroalkyl sulfonates, fluorotelomer sulfonates, perfluorocarboxylates, and select fluorinated alkyl sulfonamides. Recoveries of the fluorinated analytes from wastewater treatment plant (WWTP) raw influents and final effluent ranged from 77% – 96% and 80% – 99%, respectively. The lower limit of quantitation ranged from 0.5 to 3.0 ng/L depending on the analyte. The method was applied to flow-proportional composites of raw influent and final effluent collected over a 24 hr period from ten WWTPs nationwide. Fluorinated alkyl substances were observed in wastewater at all treatment plants and each plant exhibited unique distributions of fluorinated alkyl substances despite similarities in treatment processes. In nine out of the ten plants sampled, at least one class of fluorinated alkyl substances exhibited increased concentrations in the effluent as compared to the influent concentrations. In some instances, decreases in certain fluorinated analyte concentrations were observed and attributed to sorption to sludge.